A - falta de - representatividade negra nos livros didáticos de filosofia do ensino médio - Rodrigues, Natália Regina (2024)
This dissertation consists of the analysis of Philosophy textbooks approved by the PNLD in 2018, highlighting the hegemonic presence of the so-called Canon, composed mostly of men, white, Euro-North Americans, and the consequent absence of black male and female philosophers from these materials., distancing Philosophy, as a curricular component, from compliance with the notorious Law 10.639/03 and presenting students with the white male standard as a representation of intellectuality. Aiming to resolve the consequences of the lack of this representation, teaching material was created that introduces students to the biography and thought produced by black Africans and their diaspora, demonstrating the silencing of knowledge produced by this portion of the population doing so. the non-existent opinion. This task was carried out primarily in light of the concepts forged by Sueli Carneiro in her thesis The construction of the Other as Non-Being as the Foundation of Being, namely: raciality/biopower device and epistemicide.